2016
DOI: 10.1002/mrd.22676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on follicular atresia and granulosa cell apoptosis in the porcine

Abstract: The accumulation of reactive oxygen species is detrimental to the health of the ovarian follicle. The protective, antioxidant properties of melatonin, an endogenous component of porcine follicular fluid, on apoptosis of granulosa cells were evaluated in this study. Porcine granulosa cells from medium-sized (3-5 mm), healthy follicles were cultured in serum-free conditions with melatonin (0, 0.01, 0.1, 1.0, 10, and 100 ng/mL) with or without its receptor antagonist, luzindole, followed by evaluation of apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…Further, MTNR1A is reportedly responsible for the anti‐apoptotic effects of Melatonin on ejaculated human spermatozoa (Espino et al, ), as well as the downstream Melatonin‐related activity following human Chorionic gonadotropin stimulation of female reproductive processes (He, Ma, et al, ). On the other hand, MTNR1B was reported to predominantly mediate the in vitro effect of Melatonin on porcine GC proliferation, apoptosis, and steroidogenesis (He, Deng, et al, ). Melatonin also improved egg‐laying rates by hens as a result of MTNR1B activity, leading to increased serum estradiol and decreased ovarian GNIHR (Gonadotropin‐inhibitory hormone receptor) expression (Jia et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, MTNR1A is reportedly responsible for the anti‐apoptotic effects of Melatonin on ejaculated human spermatozoa (Espino et al, ), as well as the downstream Melatonin‐related activity following human Chorionic gonadotropin stimulation of female reproductive processes (He, Ma, et al, ). On the other hand, MTNR1B was reported to predominantly mediate the in vitro effect of Melatonin on porcine GC proliferation, apoptosis, and steroidogenesis (He, Deng, et al, ). Melatonin also improved egg‐laying rates by hens as a result of MTNR1B activity, leading to increased serum estradiol and decreased ovarian GNIHR (Gonadotropin‐inhibitory hormone receptor) expression (Jia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, MTNR1A is reportedly responsible for the anti-apoptotic effects of Melatonin on ejaculated human spermatozoa (Espino et al, 2011), as well as the downstream Melatonin-related activity following human Chorionic gonadotropin stimulation of female reproductive processes (He, Ma, et al, 2016). On the other hand, MTNR1B was reported to predominantly mediate the in vitro effect of Melatonin on porcine GC proliferation, apoptosis, and steroidogenesis (He, Deng, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() has shown that MLT/MT1 regulates luteinizing hormone (LH) and subsequently luteinization both in bovine and mice ovaries. A group of researchers reported the anti‐apoptotic property of melatonin is by its strong ability to form affinity to its both receptors 1 and 2 in bovine (Wang et al., ) and porcine (He, Deng, Jiang et al., ; He, Deng, Shi et al., ). Moreover, the combined effect of FSH and melatonin has also been explored on pre‐antral follicle growth of caprine, in vitro , and the result revealed that the interaction of FSH and melatonin was vital for integrity and growth of follicles (Rocha et al., ).…”
Section: Research Progress Of Melatonin In Animal Reproductionmentioning
confidence: 99%
“…In this research, authors described that melatonin binds exactly to rat ovarian granulosa cell membranes with high affinity (K D = 83 PM; B max = 3.28fmol/mg protein). Furthermore, immunoblot analysis and anti-MT1 melatonin receptors antibody were used in the research Clemens et al (2001) its strong ability to form affinity to its both receptors 1 and 2 in bovine (Wang et al, 2012) and porcine (He, Deng, Jiang et al, 2016;. Moreover, the combined effect of FSH and melatonin has also been explored on pre-antral follicle growth of caprine, in vitro, and the result revealed that the interaction of FSH and melatonin was vital for integrity and growth of follicles (Rocha et al, 2013).…”
Section: Melatonin Receptormentioning
confidence: 99%